2022
DOI: 10.1101/2022.09.13.507846
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell spatial analysis identifies regulators of brain tumor initiating cells

Abstract: Glioblastomas (GBMs) are aggressive brain tumors with extensive intratumoral heterogeneity. Here, we used spatial transcriptomics and single-cell ATAC-seq to dissect the transcriptome of distinct anatomical regions of the tumor microenvironment. We identified numerous extracellular matrix (ECM) molecules including biglycan elevated in areas infiltrated with brain tumor-initiating cells (BTICs). Single-cell RNA sequencing showed that the ECM molecules were differentially expressed by cells including injury resp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Cluster 2 was localized to known tumoral regions (Fig. 2F) aligning with the highly proliferative regions observed in H&E-stained slides reported in our previous study (6). Differential expression analysis (DEA) identified differences in GEPs between tumoral spots identified by InferCNV compared to non-tumoral spots within spatial datasets.…”
Section: Single-cell and Spatially Resolved Transcriptomic Profiling ...supporting
confidence: 81%
See 3 more Smart Citations
“…Cluster 2 was localized to known tumoral regions (Fig. 2F) aligning with the highly proliferative regions observed in H&E-stained slides reported in our previous study (6). Differential expression analysis (DEA) identified differences in GEPs between tumoral spots identified by InferCNV compared to non-tumoral spots within spatial datasets.…”
Section: Single-cell and Spatially Resolved Transcriptomic Profiling ...supporting
confidence: 81%
“…Written informed consent was obtained from all patients prior to the collection of tumor biopsies. The information of patients related to these specimens was described previously (6,39).…”
Section: Human Gbm Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…14,24,44 A study has shown biglycan can affect the expression of β-catenin in the cytoplasm, cell membrane and nucleus of osteosarcoma cells. 45 In 2023, Mirzaei et al 46 reported that elevated levels of biglycan in areas infiltrated with brain tumour-initiating cells (BTICs), and the overexpression of biglycan induced the proliferation rate of BTICs, possibly involved in LRP6 binding and activation of the Wnt/β-catenin pathway. Our above results also suggested the close relation between biglycan and Wnt/β-catenin pathway in hair biology.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%